Hegemony and Sustainability. A Call for Historical Materialism - Sergio D'Agata (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
Social scientists have been critical about sustainability from its appearance. However, as the literature on post-politics highlight, they have failed to address why our society endures in unsustainability in what some authors call the post-ecological paradox. This article reflects on some of the major theoretical assumptions of urban political ecology, presenting the urban sustainability fix framework as the most valuable tool to perform a critique of sustainability. It adds to the debate arguing that empirical obstacles are related and rooted in theoretical incompatibility between neo-Marxist and post-structural literatures which shape the discipline, stating the need for a return to historical materialism starting by Antonio Gramsci. To this end, the article proposes to use Jessop’s RSA to analyse sustainable development.